2021
DOI: 10.3390/antiox10020158
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Alleviates Spleen Oxidative Damage Induced by Acute Intraperitoneal Exposure to T-2 Toxin by Activating Nrf2 and Inhibiting MAPK Signaling Pathways

Abstract: T-2 toxin, which is mainly produced by specific strains of Fusarium in nature, can induce immunotoxicity and oxidative stress, resulting in immune organ dysfunction and apoptosis. Betulinic acid (BA), a pentacyclic triterpenoids from nature plants, has been demonstrated to possess immunomodulating and antioxidative bioactivities. The purpose of the study was to explore the effect of BA on T-2 toxin-challenged spleen oxidative damage and further elucidate the underlying mechanism. We found that BA not only amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…Interestingly, Shen et al ( 2019 ) recently reported that the suppression of the nuclear factor-kappa B pathway increased downstream oxidant effectors, thereby promoting the generation of reactive oxygen species (ROS) in BA-stimulated multiple myeloma cells. Although BA is known to have antioxidant activity that blocks the accumulation of ROS due to oxidative stress in normal cells (Cheng et al 2019 ; Cheng et al 2019 ; Kong et al 2021 ), their results well support the previous studies that BA promotes ROS production in cancer cells (Wang et al 2017 , 2019 ; Xu et al 2017 ; Goswami et al 2018 ; Shen et al 2019 ). However, the underlying anti-cancer mechanism of BA and associated molecular targets and the role of ROS are poorly identified in multiple cancer types.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, Shen et al ( 2019 ) recently reported that the suppression of the nuclear factor-kappa B pathway increased downstream oxidant effectors, thereby promoting the generation of reactive oxygen species (ROS) in BA-stimulated multiple myeloma cells. Although BA is known to have antioxidant activity that blocks the accumulation of ROS due to oxidative stress in normal cells (Cheng et al 2019 ; Cheng et al 2019 ; Kong et al 2021 ), their results well support the previous studies that BA promotes ROS production in cancer cells (Wang et al 2017 , 2019 ; Xu et al 2017 ; Goswami et al 2018 ; Shen et al 2019 ). However, the underlying anti-cancer mechanism of BA and associated molecular targets and the role of ROS are poorly identified in multiple cancer types.…”
Section: Introductionsupporting
confidence: 76%
“…Excessive accumulation of ROS can lead to cell cycle arrest and apoptosis through the regulation of various pathways (Moloney and Cotter 2018 ; Rodrigues and Ferraz 2020 ). After referencing a lot of literature, we found that BA can induce ROS formation in cancer cells (Wang et al 2017 , 2019 ; Xu et al 2017 ; Goswami et al 2018 ; Shen et al 2019 ), but may reduce ROS production in normal cells (Cheng et al 2019 ; Cheng et al 2019 ; Kong et al 2021 ), which means that BA has potent antioxidant activity in normal cells. Therefore, we measured the ROS content after BA treatment and found that BA was able to effectively increase ROS production at the initial time point of BA treatment, which was directly involved in BA-induced G2/M phase arrest and apoptosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that BA attenuates oxidative stress by activation of the Nrf2 signaling pathway [ 23 , 50 ]. Our results showed that BA treatment significantly increased Nrf2 transcriptional activity but showed no effect on Nrf2 expression [ 25 ], subsequently ameliorating hyperglycemia-mediated ROS generation, 8-oxo-dG formation and MG formation, and decreased the GSH/GSSG ratio in the circulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinases (MAPKs), including ERK1/2, JNK, and p38 MAPK, are evolutionarily conserved enzymes that connect cell surface receptors and intracellular regulatory targets (84,85). MAPK inhibition protects cells from oxidative stress (86). Previous studies have found that HN protected neurons by inhibiting JNK and p38 MAPK (87)(88)(89).…”
Section: Hn and The Jnk/p38 Mapk Signaling Pathwaysmentioning
confidence: 99%